ATTITUDES AND BEHAVIORS RELATED TO ORAL HEALTH IN YOUNG PARAGUAYAN ASPIRING SOLDIERS. A CROSS-SECTIONAL STUDY - Díaz-Reissner, Clarisse (2025)
Objective: To associate attitudes and behaviors related to oral health with the experience of dental caries in trainees of the Paraguayan Air Force's Airborne Brigade in the year 2023. Materials and methods: The design was cross-sectional. The sample comprised 100 soldiers. The Hiroshima University Dental Behavior Inventory (HU-DBI) was applied to measure attitudes and behaviors related to oral health, and the experience of caries was assessed using the DMFT index. The Pearson Chi-square test was used to compare the distribution of HU-DBI and DMFT according to background, and Fisher's exact test was applied to associate the experience of caries with attitudes and behaviors at a 95% confidence level. Results: Regarding the assessment of attitudes and behaviors, the average score was 6.33 (SD=1.97), classified as "fair," with a minimum score of 2 and a maximum of 11. The DMFT index was 5.45 (SD=3.9). A homogeneous distribution was found between attitudes and behaviors (p=0.197), and there was no association between caries experience and background (p=0.615). No association was found between caries experience and attitudes and behaviors (p=0.577). Conclusion: The attitudes and behaviors regarding oral health were fair, and the experience of dental caries measured by the DMFT index was low. No association was found between the two variables.